THE PRAXIOLOGICAL LINGUISTIC PICTURE OF THE WORLD ABOUT THE AGRICULTURAL WORKERS IN PHILOSOPHICALEDUCATIONAL ASPECT - Ашиток, Н. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article changes in praxiological linguistic picture (names of agricultural workers) are investigated and reasons for those changes are explained in the context of economy and education development.